Poststenotic Distal Caliber Reduction Predicts Very High-Grade Proximal Internal Carotid Artery Stenosis - von Reutern, Gerhard Michael; Perren, Fabienne; Alpsoy, Ilona; Allendörfer, Jens (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Background Angiography relates the residual lumen to the poststenotic distal lumen (NASCET criterion) and expresses the result in percent lumen reduction. This method is not applicable when there is a collapse of the distal lumen, as seen in severe stenosis. The purpose of this study was to evaluate whether the reduced poststenotic caliber could be an additional sonographic criterion for estimation of the degree of stenosis.Methods We measured the caliber of the distal lumen of the extracranial internal carotid artery (ICA) in 57 patients with low-grade stenosis <50% (NASCET criterion), and in 57 patients with unilateral stenosis of ≥ 50 %. All were classified following international recommendations. The criteria used included the poststenotic velocity to discriminate moderate to high-grade stenosis (50–70%) from very high-grade (≥ 80 %) stenosis. In addition, we measured the interrater reliability of the ultrasonic measurement of the lumen in the distal ICA.Results In the group of patients with 50% to 70% stenosis, the distal lumen was 4.3 ± 0.6 mm. In the group with very high-grade stenosis ≥ 80%, the distal lumen was 2.6±0.5mm (p<0.0001). A distal lumen of 3.2 mm or less predicted a very high-grade stenosis with a sensitivity of 0.92 and a specificity of 0.96 (AUC 0.986; 95% CI 0.97–1.00; p=0.0001).Conclusion The distal poststenotic lumen is an additional ultrasonic criterion to discriminate a very high-grade ICA stenosis from a lesser degree of ICA stenosis. It can help avoid misinterpretation due to the high variability of intrastenotic peak systolic velocities (PSV) in very high-grade ICA stenoses.
Keywords: internal carotid artery; vessel diameter; flow velocity; duplex sonography; carotid stenosis